Nature of Blame in Patient Safety Incident Reports: Mixed Methods Analysis of a National Database - Cooper, Jennifer (Ann Fam Med, 2017)
PURPOSE: A culture of blame and fear of retribution are recognized barriers to reporting patient safety incidents. The extent of blame attribution in safety incident reports, which may reflect the underlying safety culture of health care systems, is unknown. This study set out to explore the nature of blame in family practice safety incident reports. METHODS: We characterized a random sample of family practice patient safety incident reports from the England and Wales National Reporting and Learning System. Reports were analyzed according to prespecified classification systems to describe the incident type, contributory factors, outcomes, and severity of harm. We developed a taxonomy of blame attribution, and we then used descriptive statistical analyses to identify the proportions of blame types and to explore associations between incident characteristics and one type of blame. RESULTS: Health care professionals making family practice incident reports attributed blame to a person in 45% of cases (n = 975 of 2,148; 95% CI, 43%–47%). In 36% of cases, those who reported the incidents attributed fault to another person, whereas 2% of those reporting acknowledged personal responsibility. Blame was commonly associated with incidents where a complaint was anticipated. CONCLUSIONS: The high frequency of blame in these safety, incident reports may reflect a health care culture that leads to blame and retribution, rather than to identifying areas for learning and improvement, and a failure to appreciate the contribution of system factors in others’ behavior. Successful improvement in patient safety through the analysis of incident reports is unlikely without achieving a blame-free culture.